Language of citation and publishing performance of graduate students in French-speaking countries with different economic and linguistic advantages - Rassim Khelifa; Hayat Mahdjoub; Affef Baaloudj; Sara Chaib (Canadian Science Publishing, 2022)
The performance of graduate students in research varies greatly across countries due to various factors, mainly socioeconomic and linguistic. The current situation is critical because the wealthiest countries are also the most linguistically equipped to navigate the English-dominant landscape of academia. Here, we assess the language of citations and the publishing performance of graduate students from three French-speaking countries: Algeria, Canada, and France, where Algeria is the least English proficient and the most economically disadvantaged. We found that the bibliography of PhD theses were English dominated in all regions (72.5% in Algeria compared with >93.1% in Western countries), whereas those of Masters theses were French dominated in Algeria (63.3%), relatively bilingual in France (47.6% French), but English dominated in Canada-Québec (94.7%) and Canada-BC (98.7%). Algerian PhD students produced fewer papers, were less likely to publish in journals with calculated impact factors, and received fewer citations than students who graduated from universities in France or in two Canadian provinces, British Columbia and Québec. Our results suggest that the economic and linguistic disadvantages faced by graduate students from non-Western backgrounds affect their academic performance, highlighting important issues in facing future global challenges.